Concept of Time in the Poetry of Abdulhaq Hamid: Abdülhak Hamid'in Şiirlerinde Zaman İncelenmesi (Journal of the College of Languages (JCL), 2022)
After Organization literature era, two literary schools appeared in Turkey and Abdulhaq Hamid is one of this period most prominent poets. During his stay in France with a group of colleagues sent by Turkish Government, he was greatly influenced by the French modern literature and the French modern literary authors. The study discusses the concept of time in the poetry of Abdulhaq Hamid. Reading his poetry, it can be noticed that time is important where he frequently refers to day and night, morning and evening as time insinuations. Hence, the present paper gives a brief study of the poet’s life, and sheds lights on his poems that deal with time- concept.Ön Söz Tanzimat Edebiyatı döneminden sonra iki edebi okul kurulmaya başlamıştır. Bunlardan Şinasi, Ziya Paşa ve Namık Kemal okuldur. İkinci okul ise Ekrem, Hamit ve Sezai'nin okuldur. Bu edebi okulun en meşhur yazarlarından biri Abdülhak Hamit'tir. Hamit, Avrupai Türk edebiyatına etkilenmiştir. Bu edebiyatçı Fransa'ya giderken pek çok Fransız edebiyatçılarla temas etmiştir. Söz konumuz Abdülhak Hamid'in şiirlerinde Zamanı gelince şair yazdığı kasidelerinde zamanı pek çok ele almıştır.Tezin metinde zamanı nasıl nitelenmiş ve nasıl kullandığı incelemeye çalışağız. Ayrıca bu yazar yazdığı eserleri bakınca zamana pek çok önem vermiştir.